Acute exposure to diisopropylfluorophosphate in mice results in persistent cognitive deficits and alterations in senescence markers in the brain - Terry, Alvin V.; Beck, Wayne D.; Zona, Victoria; Itokazu, Yutaka; Tripathi, Ashutosh; Madeshiya, Amit Kumar; Pillai, Anilkumar (Frontiers in Neuroscience, 2024)
Organophosphates (OPs) are found in hundreds of important products used worldwide; however, they have been associated with adverse long-term health consequences ranging from neurodevelopmental deficits to age-related neurological diseases. OP exposure has also been implicated in Gulf War Illness; a cluster of medically unexplained chronic symptoms estimated to affect 25–32% of veterans of the Persian Gulf war in 1991. The development of multiple types of chronic illnesses in these veterans at an early age compared to the general population has led to the suggestion that they are experiencing signs of premature or accelerated aging. The process of cellular senescence and the development of the senescence-associated secretory phenotype (SASP) is believed to lead to chronic inflammation, chronic illnesses, as well as accelerated biological aging, and a role of environmental exposures in these processes has been suggested, but not extensively studied to date. In the studies described here, we evaluated the persistent effects of a single (acute) exposure of a representative nerve agent OP, diisopropylfluorophosphate (DFP) 4.0 mg/kg on cognitive function, noncognitive behaviors, cellular senescence markers and proinflammatory cytokines in the mouse brain. The results indicated modest, but persistent DFP-related impairments in spatial learning and working memory, but not contextual or cued fear conditioning. DFP exposure was also not associated with negative effects on weight or impairments of the various noncognitive (e.g., motor function or exploratory activity) behavioral assessments. Both histology and quantitative PCR experiments indicated that DFP was associated with persistent alterations in several senescence markers and proinflammatory cytokines in brain regions that are relevant to the performance of the memory-related tasks (e.g., hippocampus, prefrontal cortex). The results thus suggest that single acute exposures to OPs like DFP can lead to persistent impairments in specific domains of cognition that may be related to alterations in cellular senescence and inflammaging in the brain.